Sikap Bidan Terhadap Pelaksanaan Pijat Perineum - Enny Yuliaswati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Perineal rupture that happens during labor contributes for 40% -60% to post-partum hemorrhage. Complications that might occur because the perineal rupture are the longer duration of treatment, the decreasing quality of life for women, the usage of analgesic medicine, and the occurrence of incontinency alvi. The method that can reduce the occurrence of perineal rupture during labor such as perineal massage can be done during pregnancy. However, not all midwives perform perineal massage with many reasons.Objective: The purpose of this study was to analyze the differences in attitudes among midwives who did and did not do perineal massageMethod: The design of this study was a mixed method eksplanatories strategy with cross-sectional observational analytic approach to the 32 midwives who performed perineal massage and 68 midwives who did not perform perineal massage. This study was conducted in Surakarta in October-November 2012 with questionnaire which tested the reliability and validity, while Qualitative data collection using in-depth interviews. Quantitative data analysis used the Mann-Whitney test, while the qualitative data analysis be done through transcription, coding, categories, and build themes.Result: The results showed a median score of midwives’ median scores of midwives’ attitudes who performed perineal massage 75.6, did not perform it 77.5 (ZM-W = 1.491, p = 0.136). Based on a qualitative analysis of the dominant factors that caused the midwives did not perform perineal massage were factors of knowledge, motivation and culture.Conclution: It is concluded that the attitudes among midwives who performed perineal massage and did not showed any difference.Keywords: attitude, perineal massage